Measuring the impact of financial taxation on capital: Evidence from Chilean manufacturing plants - Juan A. Correa; Miguel Lorca; Francisco Parro (Journal of Applied Economics, 2019)
Using panel data from Chilean manufacturing plants, we estimate the impact of a stamp tax, levied on loans by financial institutions, on capital stock. Our results show that the tax has a statistically significant negative effect on the stock of capital. Specifically, we find that a rise of one percentage point in the financial tax rate decreases the stock of capital by about 4%. We also find that the impact on firms is heterogeneous, depending on the intensity of the different types of capital they hold. In particular, the demand for capital from firms with a higher percentage of structural assets, such as land and buildings, is relatively less affected by the tax.
Keywords: 330; Financial transaction tax; manufacturing industry; stock of capital